Situation Report: Hungary, 5 October 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Introduction of New Basic Wage System New Limitations on Real Estate and Land Ownership Danube-Tisza Canal Suggested Students Criticize Information Provided by Press, Radio, and Television Anniversary of the Chinese Revolution - As Seen from Budapest World Hunting Exhibition Closes Start of the Grape Harvest